Socialization of Tips for Increasing MSME and Educator Income Through the Utilization of Meta AI: Pengabdian - Hartana; Didik Suhariyanto; Sri Wanti Belani; Muslihatul Hidayah4; Dona Katarina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The use of artificial intelligence (AI) has become a major catalyst in digital economic transformation and pedagogical innovation. This community service activity aims to disseminate tips for increasing income for Micro, Small, and Medium Enterprises (MSMEs) and educators through the use of Meta AI. This program was implemented across islands in four specific locations: Tanjung Binga Village (Sumatra), Teluk Lerong Village (Kalimantan), Panggungharjo Village (Java), and Salassae Village (Sulawesi). The methods used included interactive workshops, technical assistance on the use of Meta AI's generative features for marketing content, and optimization of virtual assistants in creating monetization-based teaching materials. The results of the activity showed an 85% increase in digital literacy among participants and a readiness to adopt AI technology for operational strategies. The use of Meta AI has been proven to reduce marketing content production costs by up to 60%, which directly has the potential to increase profit margins for MSMEs and provide additional income opportunities for educators through the creation of educational digital products.